Second list of angiospermic taxa of Bangladesh not included in Hooker's 'Flora of British India' and Prain's 'Bengal Plants': Series I - Rahman, M Oliur (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 77-82, 2004 (June)